How Should We Secure Our Transplanted Meniscus? A Meta-analysis. Issue 9 (July 2018) - Jauregui, Julio J.; Wu, Zhan Dong; Meredith, Sean; Griffith, Cullen; Packer, Jonathan D.; Henn, R. Frank
Background: Meniscal allograft transplant (MAT) is a salvage procedure for young patients with symptomatic meniscal deficiency. Although many studies report good outcomes, MAT remains controversial, and an optimal fixation technique for the meniscus roots is debated. Purpose: To assess the overall outcome of MAT and compare the results of different meniscal root fixation techniques. Study Design: Meta-analysis. Methods: Following specific guidelines, we systematically evaluated all current literature for studies reporting on the outcomes of patients who underwent MAT. Using random effect models of proportions, we determined the tear and failure rates. Standardized mean differences (SMDs) were calculated to determine the improvement in clinical outcomes and pain level. Data were then stratified by root fixation method into 2 groups: fixation that preserved the graft's root insertions on the allograft bone (bone fixation group) and suture fixation of the root soft tissue without the allograft bone (soft tissue suture group). Results: A total of 38 studies (1637 MATs, 81% men) involving subjects with a mean age of 34 years (range, 20-48 years) and a mean follow-up of 60 months (range, 25-168 months) met inclusion criteria. This overall cohort had significant improvements in Lysholm scores (from 57.8 to 81.4 points; SMD 1.5, P < .001) and pain level (visual analog scale [VAS], from 56 to 21 points; SMD 1.8, P < .001). The cohort had a tear rate of 9% and a failure rate of 12.6%. No significant differences were found between the soft tissue suture (485 MATs) and bone fixation (489 MATs) groups in terms of meniscal allograft tear rates (13.4% vs 14.9%), failure rates (17.6% vs 18.8%), Lysholm scores (from 52.3 to 82.4, SMD 2.0, and from 60.7 to 82.9, SMD 1.7; respectively), and VAS scores (from 65 points to 18 points, SMD 2.6, and from 63 points to 13 points, SMD 3.1; both P < .001). Meniscal extrusion was similar, with a weighted mean percentage of extrusion of 40.2% in the soft tissue suture group and 43.1% in the bone fixation group. Conclusion: This meta-analysis demonstrated significant improvements in clinical outcomes for MAT patients with low tear and failure rates. The data do not demonstrate a difference between soft tissue suture and bone fixation for MAT root fixation. This suggests that the technique of root fixation may not have an appreciable influence on clinical outcome, pain reduction, extrusion, or MAT longevity. Further prospective trials are needed.